A Comparative Analysis of Media Coverage of Mass Public Shootings: Examining Rampage, Disgruntled Employee, School, and Lone-Wolf Terrorist Shootings in the United States. (December 2019) - Silva, Jason R.; Capellan, Joel A.
This study provides a comparative analysis of news media coverage across four types of mass public shootings: rampage, disgruntled employee, school, and lone-wolf terrorist. This research analyzes the agenda-setting function of the media and identifies differences in coverage and the salience of coverage, proportionality of coverage, changes in coverage over time, and factors influencing levels of coverage. Findings indicate school shootings and lone-wolf terrorist shootings receive disproportionate amounts of news media coverage. This suggests media coverage may be contributing to setting the public and policy agenda concerning the phenomenon. These findings have important implications for public perceptions of risk, conceptualizations of potential perpetrators, and the implementation of security measures.